2015
DOI: 10.1111/ctr.12587
|View full text |Cite
|
Sign up to set email alerts
|

Elevated resting heart rate in heart transplant recipients: innocent bystander or adverse prognostic indicator?

Abstract: Heart transplant recipients with elevated resting HR appear to have higher mortality than those with lower resting HR. Whether pharmacologically lowering the HR would result in better outcomes warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
(22 reference statements)
0
1
1
Order By: Relevance
“…Despite its detrimental effect on the exercise capacity of HTx patients, beta‐blocker treatment might be of benefit. Compared to other studies, a relatively high proportion of patients in our cohort were prescribed beta blockers (51.7% at M1, 66.4% at M12). There are three possible explanations for this: (a) Assumption that increased HR predicts worse outcomes in cardiovascular disease could be associated with over‐prescription of beta blockers to achieve resting HR <95‐100/min; (b) favoured beta blockers for the treatment of symptomatic atrial ectopy which can be indirectly suggested by higher frequency of atrial premature complexes on 24‐hour ECG Holter observed at 1 month in patients treated with beta blockers; (c) preference of beta blockers in combination treatment of arterial hypertension.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Despite its detrimental effect on the exercise capacity of HTx patients, beta‐blocker treatment might be of benefit. Compared to other studies, a relatively high proportion of patients in our cohort were prescribed beta blockers (51.7% at M1, 66.4% at M12). There are three possible explanations for this: (a) Assumption that increased HR predicts worse outcomes in cardiovascular disease could be associated with over‐prescription of beta blockers to achieve resting HR <95‐100/min; (b) favoured beta blockers for the treatment of symptomatic atrial ectopy which can be indirectly suggested by higher frequency of atrial premature complexes on 24‐hour ECG Holter observed at 1 month in patients treated with beta blockers; (c) preference of beta blockers in combination treatment of arterial hypertension.…”
Section: Discussioncontrasting
confidence: 66%
“…Current data on the effects of increased resting HR on all‐cause mortality in HTx patients and CAV development are contradictory. While there is relatively uniform evidence of tachycardia‐related effects on mortality, the impact on CAV development is less clear . Due to small sample sizes, retrospective and observational approaches, and overall design, previous studieshave failed to produce convincing data on the role of tachycardia in CAV development.…”
Section: Discussionmentioning
confidence: 99%